2017
DOI: 10.1080/02640414.2017.1385264
|View full text |Cite
|
Sign up to set email alerts
|

Development and initial validation of an instrument to assess stressors among South African sports coaches

Abstract: The aim of this series of studies was to develop and initially validate an instrument to assess stressors among South African sports coaches. In study one, a preliminary pool of 45 items was developed based on existing literature and an expert panel was employed to assess the content validity and applicability of these items. In study two, the 32 items that were retained after study one were analysed using principal component analysis (PCA). The resultant factorial structure comprised four components: environm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 39 publications
1
4
0
Order By: Relevance
“…Stressors regarding logistics and operations, and coaching were the least experienced by both players and coaches in the Ghana premier league. The current findings on the prevalence of The finding that the Ghana premier league players and coaches experienced stressors in their work is similar to the findings of other studies conducted in the United States of America (USA), United Kingdom (UK), Australia and Europe (Hanton et al, 2005;Thelwell et al, 2008Thelwell et al, , 2016aMellalieu et al, 2009;Fletcher and Scott, 2010;Kristiansen et al, 2012;Thelwell, 2012;Didymus, 2017), and South Africa (Kubayi et al, 2018). For example, Didymus (2017) found that coaches experienced many stressors in relation to selection, athlete concerns, coaching responsibilities, expectations, interference, preparation, organizational management, and performance among others.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Stressors regarding logistics and operations, and coaching were the least experienced by both players and coaches in the Ghana premier league. The current findings on the prevalence of The finding that the Ghana premier league players and coaches experienced stressors in their work is similar to the findings of other studies conducted in the United States of America (USA), United Kingdom (UK), Australia and Europe (Hanton et al, 2005;Thelwell et al, 2008Thelwell et al, , 2016aMellalieu et al, 2009;Fletcher and Scott, 2010;Kristiansen et al, 2012;Thelwell, 2012;Didymus, 2017), and South Africa (Kubayi et al, 2018). For example, Didymus (2017) found that coaches experienced many stressors in relation to selection, athlete concerns, coaching responsibilities, expectations, interference, preparation, organizational management, and performance among others.…”
Section: Discussionsupporting
confidence: 88%
“…The authors indicated that football coaches are the ones who usually set standards and control all activities in the team. Additionally, Fletcher and Scott ( 2010 ) and Kubayi et al ( 2018 ) suggested that there is a high demand on coaches concerning what they do on key matters such as squad and team selection, athletes' wellbeing and performance, organization and administrative tasks while they try to improve their own performances (Gould et al, 2002 ). Similar evidence was revealed in Thelwell et al's ( 2016a ) study on the perceptions of athletes on stress experienced by their coaches in elite sports environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the context of sport, coaching is increasingly acknowledged as a stressful occupation (Carson et al, 2019;Frey, 2007;Kelley et al, 1999;Levey et al, 2009). Literature examining coach stress has typically focused on elite settings (see Didymus, 2017;Fletcher & Scott, 2010;Ntwanano et al, 2017) with a range of stressors identified, including organisational stressors; scrutiny from parents, public, and the media; the demands and expectations of the coach role; athletes' performance; athlete injury, coachability, professionalism, attitude, and commitment (Norris et al, 2017). There is a significant positive relationship between the frequency of organisational stressors and burnout, surface acting (i.e., emotional displays that do not reflect an individual's true feelings), and subjective performance (Arnold & Fletcher, 2021).…”
Section: Exploring the Daily Hassles Of Neophyte Cycling Coachesmentioning
confidence: 99%
“…The BSCQW was underpinned by LaVoi and Dutove's (2012) ecological model. To help develop an initial item pool, a review of literature relating to the barriers experienced by women coaches was conducted (see e.g., Kamphoff & Gill, 2008;Kubayi et al, 2017;Kubayi et al, 2018;LaVoi & Dutove, 2012;Surujlal & Vyas-Doorgapersad, 2015). During this review, literature was searched for, reviewed, and aligned to one of the four levels of the ecological model.…”
Section: Measurementioning
confidence: 99%